PERAN KOMUNIKASI ASERTIF DALAM MENGHINDARI KONFLIK RUMAH TANGGA KRISTEN - Gomgom Purba; Mariani Ruslianty (JURNAL TABGHA, 2023)
Abstract A household or marriage is part of God's great plan for His human creation according to Genesis 1:26-28. The essence of the household is to unite two people who have a variety of differences because they were born and raised in different families. However, it is not uncommon to find so many divisions in the household that are often caused by weak communication between husband and wife, as well as children in the household. Therefore researchers are trying to find assertive communication solution methods as problem solvers that arise in the household. Because every problem that exists must be resolved by means of proper and effective communication. This research is a qualitative research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. Despite the success of the role of assertive communication in avoiding conflict in Christian households, the role of management is very important. Assertive communication is a good solution for housewives and it is very good to be applied in the household in order to solve problems. Keywords: Communication, Assertive, Solution, Conflict, Household.